(untitled) (International Journal of Engineering and Computer Science, 2017)
Adhoc network, because of dynamic behavior, self sustaining approach, and non-reliability of infrastructure has made this network a major communication approach for future usage. These networks are benefited by adaptive node integration and dynamic routing for data exchange. Adaptive routings has high significance of data exchange, with adaptive network performances such as high throughput, low power dissipation, less interference, and long lasting networks. However with the advantage of having dynamic routing behavior in adhoc network, optimal routing and its selection remains an open issue to solve. To achieve the objective of optimal routing based on node characteristic and network property, various methods were developed in past. This paper, outlines the methods developed towards secure routing for robust and reliable routing in wireless adhoc network.